2015
DOI: 10.1111/pde.12650
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Chikungunya—A Cause of Neonatal Hyperpigmentation

Abstract: A 12-day-old neonate presented with ill-defined dark pigmentation over the centrofacial area with flagellate pigmentation on the trunk and patchy pigmentation on the extremities. The mother had a history of fever starting a week before delivery and continuing for 3 days in the postpartum period. Together these led to consideration of a possible diagnosis of congenital chikungunya, which was confirmed according to the immunoglobulin M antibodies to chikungunya in the mother and child. The rare occurrence of cut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 7 publications
0
23
0
Order By: Relevance
“…1,5 Hyperpigmentation areas in the face, chest, shoulder, and the palm of the hand may also occur. 7 In a previous study, 1,400 pregnant women were enrolled during a CHIKV outbreak in the Reunion Island (628 uninfected, 658 infected during pregnancy, 27 infected before pregnancy, and 87 infected on unknown dates). Outcomes (cesarean deliveries, obstetric hemorrhaging, preterm births, and stillbirths after 22 weeks, birth weight, congenital malformations, and newborn admissions) were similar between the groups.…”
Section: Casementioning
confidence: 99%
“…1,5 Hyperpigmentation areas in the face, chest, shoulder, and the palm of the hand may also occur. 7 In a previous study, 1,400 pregnant women were enrolled during a CHIKV outbreak in the Reunion Island (628 uninfected, 658 infected during pregnancy, 27 infected before pregnancy, and 87 infected on unknown dates). Outcomes (cesarean deliveries, obstetric hemorrhaging, preterm births, and stillbirths after 22 weeks, birth weight, congenital malformations, and newborn admissions) were similar between the groups.…”
Section: Casementioning
confidence: 99%
“…However, evidence suggested that viable infective virus is excreted in the saliva of monkeys, mice, and humans, and it could be a source of infection particularly in immunocompromised patients [32,33]. Vertical transmission has also been reported [34,35]. Despite some studies failed to show effect of CHKV infection during pregnancy on major obstetrical outcomes or congenital anomalies, long-term follow-up studies have reported poor neurocognitive outcomes of newborns and even poorer results in patients with neonatal CHIKV encephalopathy [36,37].…”
Section: Pathogenesis and Disease Transmissionmentioning
confidence: 99%
“…There are differences in the clinical presentation of infants and adults with chikungunya. Infants have an abrupt onset of fever lasting 1 day, followed by the development of maculopapular rash [10]. The common sites of pigmentation in chikungunya fever include the nose, trunk, face, shoulders (shawl-like distribution), and palms.…”
Section: Resultsmentioning
confidence: 99%
“…Chikungunya can be added to the list of viral infections that can lead to fetal demise or, when present during labor and delivery, can cause neonatal disease with cutaneous signs. Vasani et al [10] reported a case of 12 day old neonate presented with ill-defined dark pigmentation over the centrofacial area with flagellate pigmentation on the trunk and patchy pigmentation on the extremities. The mother had a history of fever starting a week before delivery and continuing for 3 days in the postpartum period.…”
Section: Post-chikungunya Pigmentation In a Neonatementioning
confidence: 99%
See 1 more Smart Citation